Penerapan Media Pembelajaran Scrapbook Berbasis Nilai Keislaman pada Pembelajaran PPKn Kelas II MI NU Nahdlatus Shibyan Ngemplak Undaan Kudus - Annisa Dita Ramadhani Sutiono; Elya Umi Hanik (Paedagogie: Jurnal Pendidikan dan studi Islam, 2023)
This study aims to find out clearly about the application of Islamic value-based scrapbook learning media in Pancasila and Citizenship Education (PPKn) learning, to determine the supporting and inhibiting factors of learning, as well as the successful application of Islamic values-based scrapbook learning media in PPKn learning class II MI NU Nahdlatus Shibyan Ngemplak Holy Invitation. This research is a qualitative research using the type of field research (field research). The subjects of this research are class II teachers and class II students with data collection methods, namely by conducting observations, interviews, and documentation. The results of this study are the application of Islamic value-based scrapbook learning media in Civics learning with several stages, namely the planning stage, implementation stage and learning evaluation stage. There are learning supporting factors, namely healthy physical condition, teacher's ability to teach, learning motivation, student activity, and facilities and infrastructure, while learning inhibiting factors are differences in student characteristics and learning time. Some of these learning stages are able to increase learning motivation with several indicators, namely concentration on learning, high curiosity, enthusiasm, readiness, and self-confidence as well as increasing religious values ​​with indicators of Islamic values, namely faith values, worship values, and moral values.